El Derecho como un instrumento generacional y dinámico al servicio de la sociedad: un acercamiento desde la óptica Holmesiana (2018)
The present text addresses from a Holmesian reading the Law and its dynamic role at the service of society, rejecting any approach that becomes an obstacle for future generations. Considering in this sense that no institution, however important, can be considered as inalterable and, no law however fundamental, can be considered as irrevocable either (Holmes, 2004, p.199).Starting from the Constitution as the supreme norm, its scope is projected as aninstrument that allows it to be either a stabilizing axis of the present, or allowsit to become an obstacle for the future. This is based on the phenomenon causedby the intentions that past generations had, which is today a navigation route and which, when reflected in political documents, will therefore govern the compass that steers public decisions.